ASYNDETIC PHRASE: FEATURES OF TRANSLATION - Dzividzinska, I. S.; Bodnar, R. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the peculiarities of the attributive phrases translation from English into Ukrainian. Attributive constructions in English texts are inherent in socio-political, scientific and technical texts and occupy a significant place in the English grammar. Such structures are not typical for Ukrainian grammar, therefore, the article is devoted to the identification of their common features and peculiarities. It studies congruent structures in the Ukrainian language.